2020
DOI: 10.1002/er.5684
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of non‐linear process parameters on the prediction of hydrogen production by steam reforming of bio‐oil and glycerol using artificial neural network

Abstract: Biomass-derived substrates such as bio-oil and glycerol are gaining wide acceptability as feedstocks to produce hydrogen using a steam reforming process. The wide acceptability can be attributed to a huge amount of glycerol and bio-oil obtained as by-products of biodiesel production and pyrolysis processes. Several parameters have been reported to affect the production of hydrogen by biomass steam reforming. This study investigates the effect of non-linear process parameters on the prediction of hydrogen produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…As indicated by the R 2 of .981, the 2-LMLP neural network model can generalize 98.1% of the data set with minimal residuals (Figure 8B). The MLP model performance in this study is consistent with that reported by Karaci et al, 37 Syed et al, 38 Alsaffar et al, 39 and Mageed et al 40 for modeling hydrogen dual fueled diesel engine characteristic, hydrogen-rich syngas production from pyrolysis, prediction of carbon deposition from methane dry reforming and hydrogen-rich syngas production from bio-oil and glycerol pyrolysis, respectively. The one-layer MLP neural network model reported by Syed et al 38 was robust in predicting the characteristics of the hydrogen dual fueled diesel with a minimal prediction error.…”
Section: The Multilayer Perceptron Neural Networksupporting
confidence: 89%
See 2 more Smart Citations
“…As indicated by the R 2 of .981, the 2-LMLP neural network model can generalize 98.1% of the data set with minimal residuals (Figure 8B). The MLP model performance in this study is consistent with that reported by Karaci et al, 37 Syed et al, 38 Alsaffar et al, 39 and Mageed et al 40 for modeling hydrogen dual fueled diesel engine characteristic, hydrogen-rich syngas production from pyrolysis, prediction of carbon deposition from methane dry reforming and hydrogen-rich syngas production from bio-oil and glycerol pyrolysis, respectively. The one-layer MLP neural network model reported by Syed et al 38 was robust in predicting the characteristics of the hydrogen dual fueled diesel with a minimal prediction error.…”
Section: The Multilayer Perceptron Neural Networksupporting
confidence: 89%
“…With an R 2 of .950, the predicted hydrogen‐rich syngas was in proximity to the observed values. Similarly, the MLP neural network model was robust in predicting hydrogen production from the pyrolysis of bio‐oil and glycerol 40 . Using a topology of 3‐16‐1 for the MLP neural network model, the amount of carbon deposited on Ni catalysts during methane dry reforming was well modeled as evident by the close agreement between the predicted carbon deposited and the observed values.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, GPR has also been used to model the relationship between capacity, storage temperature, and state-of-charge (Liu et al 2020). The GPR model displayed a robust prediction performance of high accuracy and accurate generalization ability (Mageed et al 2020;Shnain et al 2022). Extensive literature search shows that the use of GPR for modeling the relationship between parameters such as the pH, salinity, and the ratio of TiO 2 /SiO 2 nanoparticle in the nanofluids and the amount of n-heptane in crude oil has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol can be converted to fuel extender 4,5 and various chemicals such as hydrogen/syngas, propanediol, acrolein, propylene glycol, and glycerol carbonate through different pathways, steam [6][7][8] /dry reforming, 9 hydrogenolysis, 10 dehydration, oxidation, and transesterification, respectively. 11 One of the most promising products is glycerol carbonate (4-hydroxymethyl-1, 3-dioxolan-2-one, CAS #931-40-8) due to its excellent biodegradability, high boiling point, high flash point, low toxicity, and water solubility.…”
Section: Introductionmentioning
confidence: 99%